General practitioners’ deprescribing decisions in older adults with polypharmacy: a case vignette study in 31 countries - Katharina Tabea Jungo; Sophie Mantelli; Zsofia Rozsnyai; Aristea Missiou; Biljana Gerasimovska Kitanovska; Birgitta Weltermann; Christian Mallen; Claire Collins; Daiana Bonfim; Donata Kurpas; Ferdinando Petrazzuoli; Gindrovel Dumitra; et al. (BMC Geriatrics, 2021)
Abstract Background General practitioners (GPs) should regularly review patients’ medications and, if necessary, deprescribe, as inappropriate polypharmacy may harm patients’ health. However, deprescribing can be challenging for physicians. This study investigates GPs’ deprescribing decisions in 31 countries. Methods In this case vignette study, GPs were invited to participate in an online survey containing three clinical cases of oldest-old multimorbid patients with potentially inappropriate polypharmacy. Patients differed in terms of dependency in activities of daily living (ADL) and were presented with and without history of cardiovascular disease (CVD). For each case, we asked GPs if they would deprescribe in their usual practice. We calculated proportions of GPs who reported they would deprescribe and performed a multilevel logistic regression to examine the association between history of CVD and level of dependency on GPs’ deprescribing decisions. Results Of 3,175 invited GPs, 54% responded (N = 1,706). The mean age was 50 years and 60% of respondents were female. Despite differences across GP characteristics, such as age (with older GPs being more likely to take deprescribing decisions), and across countries, overall more than 80% of GPs reported they would deprescribe the dosage of at least one medication in oldest-old patients (> 80 years) with polypharmacy irrespective of history of CVD. The odds of deprescribing was higher in patients with a higher level of dependency in ADL (OR =1.5, 95%CI 1.25 to 1.80) and absence of CVD (OR =3.04, 95%CI 2.58 to 3.57). Interpretation The majority of GPs in this study were willing to deprescribe one or more medications in oldest-old multimorbid patients with polypharmacy. Willingness was higher in patients with increased dependency in ADL and lower in patients with CVD.